PENGGUNAAN MEDIA SOLUTION CARD PADA MATERI DIMENSI TIGA KELAS XII SMA NEGERI 2 PONTIANAK - Fitriadi, Fitriadi; Yusmin, Edy; Munaldus, Munaldus (Universitas Tanjungpura, 2025)
This research aims to determine the differences in student mathematics learning outcomes between the experimental group and the control group on three-dimensional material. The experimental group used solution card media while the control group did not use solution card media. Then we will find out how significant the difference is. The method used is experimentation in the form of Quasi Experimental Design, with Non-equivalent Control Group. Based on the data analysis carried out, the results obtained were that the average difference for the experimental group was 24.2220 and the average difference for the control group was 8.8890. Hypothesis test results using the Independent-Samples T-test, it was obtained that the value t_statistic(9.829) > t_table(2.0017) and P-value (0.000) < Î± (0.05), so there is a difference between the two groups. Based on the calculation results, it was found that the effect size value (Cohen's